ANALISIS YURIDIS TERHADAP PENOLAKAN PENCATATAN PERKAWINAN BEDA AGAMA PASCA SEMA NOMOR 2 TAHUN 2023 - Salsabil Syakira Musadad; Hilman Nur (CV. Denasya Smart Publisher, 2026)
This study is motivated by the refusal to register interfaith marriages in Indonesia, a stance reinforced by Supreme Court Circular Letter Number 2 of 2023. This condition raises legal issues concerning legal certainty, justice, and utility for couples who are unable to officially register their marriages. This study aims to analyze the legal basis for the refusal of interfaith marriage registration and to examine its implications within the Indonesian legal system. The research method used is normative legal research with statutory, conceptual, and case approaches, utilizing primary, secondary, and tertiary legal materials analyzed qualitatively through library research. The results show that the refusal to register interfaith marriages has a strong legal basis, namely Law Number 1 of 1974 which requires marriages to be conducted according to religious law, and is further reinforced by SEMA Number 2 of 2023 as a guideline for judges. However, this policy still creates issues in terms of justice and legal utility, particularly regarding legal protection and certainty of status for couples who cannot register their marriages. Therefore, for parties who enter into interfaith marriages, a more adaptive interpretation or legal update is needed to achieve a balance between legal certainty, justice, and legal benefits.